Dimerization and lysine substitution of melittin have differing effects on bacteria - Matthyssen, Tamara; Li, Wenyi; Holden, James A.; Lenzo, Jason C.; Hadjigol, Sara; O’Brien-Simpson, Neil M. (Frontiers in Pharmacology, 2024)
Melittin is a potent antimicrobial peptide from bee venom that is effective against both Gram-positive and Gram-negative bacteria. However, it is extremely toxic to mammalian cells and as yet has no clinical use. Modifications to its amino acid sequence, cyclisation, truncation and dimerisation have been tried in order to reduce its toxicity whilst maintaining its antimicrobial activity. In this study, we targeted the three lysine residues present in melittin and substituted them with lysine homologues containing shorter side-chains (Ornithine, Orn, diaminobutyric acid, Dab, and diaminopropanoic acid, Dap), and made both parallel and antiparallel melittin dimers to observe how lysine substitution and dimerisation affects its activity and toxicity. The antibacterial activity of melittin and its analogues were tested against S. aureus (Gram-positive bacteria) and E. coli (Gram-negative bacteria), and cytotoxicity was tested against the mammalian cell lines HEK293 and H4IIE. Overall, dimerisation and lysine substitution exhibited improved antimicrobial activity towards E. coli and limited improvement towards S. aureus, however mammalian cell toxicity was only marginally reduced compared to native melittin. Interestingly, the parallel dimer was found to be marginally more active than the antiparallel dimer, indicating orientation maybe important for activity, although both dimers were less effective than the native and Lys-analogue peptides towards S. aureus. Of the Lys substitutions, Dab and Dap improved melittin's activity towards E. coli. In conclusion, dimerisation and Lys substitution of melittin improved the antimicrobial activity towards Gram-negative but not significantly towards Gram-positive bacteria. Some analogues also displayed reduced toxicity towards HEK293 and H4IIE cells but overall, remained toxic at bactericidal concentrations. Our data indicates that although highly antibacterial, melittin's toxicity is the major drawback in its potential use.